Effect of L-arginine additive on the growth and physical properties of Potassium /subihydrogen Phosphate single crystals - Kostenyukova, E.I.; Uklein, A.V.; Multian, V.V.; Pritula, I.M.; Bezkrovnaya, O.N.; Doroshenko, A.G.; Khimchenko, S.V.; Fedorov, A.G.; Levchenko, A.N.; Starikov, A.I.; Gayvoronsky, V.Ya. (Functional Materials, 2018)
Potassium dihydrogen phosphate (KDP) single crystals doped with L-arginine (L-arg) amino acid were grown from aqueous solutions onto a point seed using the temperature reduction method. The incorporation of L-arg molecules into the crystal was verified by means of ninhydrin reaction. Undoped and L-arginine doped KDP crystals were characterized by XRD method and structure perfection of the doped crystals was shown o correspond to the one of pure KDP. It was established that incorporation of L-g molecules into KDP crystal had an effect on the formation of additional bonds in the crystal structure, that manifested itself in the thermal properties of the doped crystals. Investigation of ε^/ε|| value which characterizes the dielectric permittivity anisotropy showed that it was minimal at 0.5-1.0 wt.% L-arg concentrations. In this case, the introduced L-arg seems to lead to creation of additional hydrogen bonds and disappearance of proton vacancies bound up with aliovalent impurities. Since the crystals contain different impurity defects, L-arg molecules are oriented in he lattice in a different way, depending on the type of the defects, and diminish the anisotropy. The present study testifies that the attenuation of the values of DC conductivity, dielectric permittivity and loss tangent at L-arg concentrations of 1 wt.% is probably related o the content decrease of the proton vacancies and the impurity-proton vacancy complexes dipoles, formed due to incorporation of the impurity ions into the crystal. The incorporation of L-arg molecules into the crystalline matrix results in an order of magnitude enhancement of he refractive nonlinear optical (NLO) response efficiency and its sign turn to self-focusing effect versus the self-defocusing obtained in the nominally pure KDP crystal. Similar kind of the NLO response efficiency rise in the KDP single crystals doped with TiO₂ nanoparticles. The phenomenon can produce the enhancement of the optical harmonics generation efficiency due to the laser radiation localization and improvement of phase matching conditions realization.